Pelatihan Penyusunan Laporan Keuangan Nirlaba Pada Yayasan Kaki Kota Banjarmasin Berdasarkan Psak No.45 - Bandi, Maulida Hirdianti; Putriana, Astia; Anjaswari, Gati; Hayatie, Marliza Noor; Ghalih, Muhammad (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2022)
A non-profit organization or non-profit organization is an organization whose main goal is to support an issue or matter in attracting public attention for a non-commercial purpose, without any attention to profit-making matters. Nonprofit organizations include churches, public schools, public charities, public hospitals and clinics, political organizations, legal aid organizations, volunteer service organizations, labor unions, professional associations, research institutes, museums, and some government agencies. The Foot Foundation of Banjarmasin City as a partner that collaborates in Community Service activities related to the preparation of non-profit financial reports based on PSAK No. 45 with training methods. In its implementation, there is a presentation of material regarding the preparation of non-profit financial reports based on PSAK No. 45 and continued with discussions and questions and answers with service participants. The results of this service are expected to provide insight and improve the quality of human resources, especially regarding the preparation of non-profit financial reports based on PSAK No. 45.